Justiça Restaurativa como paradigma? - Silva, Tâmisa Rúbia Santos do Nascimento (2017)
Taking the theory about the paradigms of Thomas Kuhn as an initial theoretical framework, but adapted to the scope of the human and social sciences, we investigate in the present work if it is possible to conceive the proposal of Restorative Justice as a paradigm, even in the face of the multiplicity of theoretical Characteristics and objectives. In the light of Thomas Kuhn's considerations in "The Structure of Scientific Revolutions" (1962), paradigms are models that guide the activity of "normal science", in order to establish parameters that will allow the scientific community to explain a certain phenomena and it’s necessary for it validation, that these basic parameters are accepted in a relative consensus by the scientific community. Based on this construction, we seek to affirm that the proposal of restorative justice must be understood as a paradigm, even in the face of the multiplicity of constructions about it, because it is observed in this multiplicity of views, certain basic consensual theoretical foundations (what we call hard nucleus) that allow the scientific community to reexamine how we should understand and respond to criminal conflicts. Theoretical divergences are / will be responsible for promoting the variety of theories sheltered by the paradigm; as the paradigm reaches the stage of maturity, these will tend to diminish, producing greater consensus. From this new paradigm it would be possible to construct new ideas and practices for the treatment of these conflicts. For the confirmation of this statement we will use the research method.